Non-lethal message from the Holy Land: the first international conference on nonapoptotic roles of apoptotic proteins. - Arama, E; Baena-Lopez, LA; Fearnhead, HO (Wiley, 2020)
Apoptosis is a major form of programmed cell death (PCD) that eliminates unnecessary and potentially dangerous cells in all metazoan organisms, thus ensuring tissue homeostasis and many developmental processes. Accordingly, defects in the activation of the apoptotic pathway often pave the way to disease. After several decades of intensive research, the molecular details controlling the apoptosis program have largely been unraveled, as well as the regulatory mechanisms of caspase activation during apoptosis. Nevertheless, an ever-growing list of studies is suggesting the essential role of caspases and other apoptotic proteins in ensuring nonlethal cellular functions during normal development, tissue repair, and regeneration. Moreover, if deregulated, these novel nonapoptotic functions can also instigate diseases. The difficulty of identifying and manipulating the caspase-dependent nonlethal cellular processes (CDPs), as well as the nonlethal functions of other cell death proteins (NLF-CDPs), meant that CDPs and NLF-CDPs have been only curiosities within the apoptotic field; however, the recent technical advancements and the latest biological findings are assigning an unanticipated biological significance to these nonapoptotic functions. Here, we summarize the various talks presented in the first international conference fully dedicated to discuss CDPs and NFL-CDPs and named 'The Batsheva de Rothschild Seminar on Non-Apoptotic Roles of Apoptotic Proteins'. The conference was organized between September 22, 2019, and 25, 2019, by Eli Arama (Weizmann Institute of Science), Luis Alberto Baena-Lopez (University of Oxford), and Howard O. Fearnhead (NUI Galway) at the Weizmann Institute of Science in Israel, and hosted a large international group of researchers.